Effect of Baseline Mental Health on 1-Year Outcomes After Hip Arthroscopy: A Prospective Cohort Study. Issue 8 (31st August 2021) - Lynch, T. Sean; Oak, Sameer R.; Cossell, Charles; Strnad, Gregory; Zajichek, Alexander; Goodwin, Ryan; Jones, Morgan H.; Spindler, Kurt P.; Rosneck, James
Background: Patient factors, including mental health, sex, and smoking, have been found to be more predictive of preoperative hip pain and function than intra-articular findings during hip arthroscopy for femoroacetabular impingement (FAI); however, little is known about how these factors may influence patients' postoperative outcomes. Hypothesis: We hypothesized that lower patient-reported mental health scores would be significant risk factors for worse patient-reported outcomes (PROs) 1 year after arthroscopic hip surgery for FAI and that baseline intra-articular pathology would fail to demonstrate an association with outcomes 1 year after FAI surgery. Study Design: Cohort study; Level of evidence, 2. Methods: A prospective cohort of patients undergoing hip arthroscopy for FAI were electronically enrolled. Baseline and 1-year follow-up PROs were collected, including Hip disability and Osteoarthritis Outcome Score for pain (HOOS-Pain), HOOS–Physical Function Short Form (HOOS-PS), and Veterans RAND 12-Item Health Survey–Mental Component Score (VR-12 MCS). Intra-articular operative findings and treatment were documented at the time of surgery. Proportional odds logistic regression models were built for 1-year outcomes (HOOS-Pain, HOOS-PS, and VR-12 MCS). Risk factors included patient characteristics and intraoperative anatomic and pathologic findings. Results: Overall, 494 patients underwent hip arthroscopy for FAI, and 385 (78%) were evaluated at 1 year with at least 1 PRO. The median patient age was 33 years, mean body mass index was 25.5 kg/m 2, and 72% were female. Multivariable analysis demonstrated that better baseline HOOS-Pain, HOOS-PS, and VR-12 MCS were significantly associated with improvement in the 1-year scores for each PRO. Higher VR-12 MCS was significantly associated with better 1-year HOOS-Pain and HOOS-PS, while current and former smokers had worse 1-year outcomes than those who never smoked. In ranking each variable's relative importance, baseline HOOS-Pain and HOOS-PS and baseline VR-12 MCS were identified as the strongest predictors of 1-year HOOS-Pain and HOOS-PS in our multivariable model. Conclusion: During hip arthroscopy for FAI, patient factors, including baseline hip pain and function, mental health, and smoking, were independently associated with 1-year PROs of hip pain and function, while intra-articular pathology such as the presence of labral tear and its treatment, tear size, tear location, and anchors placed were not independently associated.